Analisa Perbandingan Pengaruh Gempa terhadap Gedung Bertingkat Berdasarkan SNI 1726:2012 dan SNI 1726:2019 - Triayaska, Aviska; Trimurtiningrum, Retno (Portal: Jurnal Teknik Sipil, 2024)
Earthquakes are one of the important factors that need to be considered in planning building structures considering that Indonesia is an earthquake-prone country. Therefore, all building structures must be able to withstand vertical forces (field loads) and horizontal forces (wind and earthquake loads). In designing buildings, especially in earthquake-prone areas, the structure in receiving earthquake loads is very important to analyze. In conducting the analysis, it is necessary to have the latest earthquake regulations used as a reference, one of which is SNI 1726: 2019. This study aims to determine the effect of earthquake forces such as mass participation values, base shear force values, and inter-floor deviation values based on old earthquake regulations and the latest earthquake regulations, namely SNI 1726: 2012 and SNI 1726: 2019. The results of the analysis show that the comparison of the spectrum response values has increased the S¬a value by 5.35%, the mass participation value increased by 0.4% for the x direction and by 0.2% for the y direction, the internal force value in the x direction has a smaller percentage than the beam and column in the y direction, the base shear force value increased by 17.72% for the x direction and 16.81% for the y direction, the deviation between floors increased by 0.0583% to 0.0920%.